EFEK KADAR LUMPUR TERHADAP KEKUATAN BETON GEOPOLIMER - Djedjen Achmad (Jurnal Poli-Teknologi, 2015)
Abstract It has been tested the effects of claycontent (material through sieve No. 200) on the coarse aggregate and fine aggregate on the characteristics of geopolymer concrete. Research done on aggregate with three variations content of clay, i.e 0.94%, 2.4%, and 4.8% by weight of the combined aggregate (fine aggregate and coarse aggregate). Geopolymer concrete made with the composition of the mixture of w/b = 0.25, 10M NaOH, and ratio of Na2SiO3: NaOH = 2: 1, and the ratio between coarse aggregate: fine aggregate = 65%: 35%. In the test the workability of fresh concrete with a slump, at the age of 7, 14 and 28 day compressive strength testing, while the split tensile strength test and flexural tensile strength was tested at 28 days. From the result of research, the higher of claycontent at the aggregate, the lower the compressive strength. With the clay content of 2.4% and 4.8% at 28 days compressive strength is differences compared with 0.94% claycontent decreased by 27.52% and 50.15%. Similarly of tensile strength when compared to the tensile strength at content of 0.94% clay, the clay concentration of 2.4% and 4.8% the tensile strength decreased by 19:47 and 25.18% and flexural tensile strength at a content of 2.4% and 4,8% clay, decreased by 22:34 and 42.78%, compared to 0.94% clay content. Keywords: Concrete. geopolymer, clay, characteristics, strength Abstrak Telah diuji efek kadar lumpur (material lolos saringan No. 200) pada agregat kasar dan agregat halus terhadap karakteristik beton geopolimer. Penelitian dilakukan terhadap agregat dengan kadar lumpur bervariasi 0.94%, 2.4%, dan 4.8% terhadap berat agregat gabungan (agregat halus dan agregat kasar). Beton geopolimer dibuat dengan komposisi campuran w/b = 0,25, NaOH 10 M, dan perbandingan Na2SiO3 : NaOH = 2 : 1, serta perbandingan antara agregat kasar : agregat halus = 65 % : 35 %. Pada beton segar dilakukan uji workability dengan alat slump, pada umur 7, 14 dan 28 hari dilakukan pengujian kuat tekan, sedangkan uji kuta tarik belah dan kuat tarik lentur diuji pada umur 28 hari. Dari hasil penelitian, semakin tinggi kadar lumpur pada agregat, kuat tekannya semakin rendah. Dengan kadar lumpur 2,4% dan 4,8% pada umur 28 hari perbedaan kuat tekannya dibandingkan dengan kadar lumpur 0.94 % turun sebesar 21.3 % dan 45.8%. Demikian pula kuat tarik belahnya jika dibandingkan dengan kuat tarik pada kadar lumpur 0.94 %, pada kadar lumpur 2,4% dan 4,8% kuat tarik belahnya turun sebesar 19.47 dan 25.18 % dan kuat tarik lenturnya pada kadar lumpur 2,4% dan 4,8% turun sebesar 22.34 dan 42.78 %, dibandingkan kuat tarik lentur pada kadar lumpur 0.94 %. Kata kunci : Beton. geopolimer, lumpur, karakteristik,.kekuatan